2012
DOI: 10.7439/ijpr.v2i3.806
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Ethanolic Extract of Ficus Benghalensis on Open Wounds and Inflammation

Abstract: AbstractsThe present study deals with evaluation of antioxidant, wound healing and anti-inflammatory activity of ethanolic extract of Curcuma longa Linn rhizomes. The ethanolic extract prepared by maceration technique was subjected to screen for antioxidant activity using DPPH radical scavenging method and wound healing activity using incision, excision, histopathological and dead space wound model and the study was supported with evaluation of granuloma tissue to estimate hydroxyproline content and histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…The obtained results demonstrate the significant anti-inflammatory activity of F. microcarpa and its phenolic compounds in both COX inhibition and protein denaturation assays. These findings align with studies on other Ficus species, such as F. racemosa leaves and bark [ 34 , 35 , 36 ], F. religiosa leaves and bark [ 37 , 38 ], F. benghalensis bark [ 39 , 40 ], and F. carica [ 41 ]. The literature has documented that catechin can exert noteworthy anti-inflammatory properties by modulating the activation or deactivation of inflammation-related oxidative stress signaling pathways.…”
Section: Discussionsupporting
confidence: 89%
“…The obtained results demonstrate the significant anti-inflammatory activity of F. microcarpa and its phenolic compounds in both COX inhibition and protein denaturation assays. These findings align with studies on other Ficus species, such as F. racemosa leaves and bark [ 34 , 35 , 36 ], F. religiosa leaves and bark [ 37 , 38 ], F. benghalensis bark [ 39 , 40 ], and F. carica [ 41 ]. The literature has documented that catechin can exert noteworthy anti-inflammatory properties by modulating the activation or deactivation of inflammation-related oxidative stress signaling pathways.…”
Section: Discussionsupporting
confidence: 89%
“…The ethanolic extract of leaves of Ficus religiosa was evaluated for antioxidant (DPPH) activity. The tested extract of different dilutions in the range 200 µg/ml to 1000 µg/ml shows antioxidant activity in a range of 6.34% to 13.35% 48 . Root extracts showed significant antioxidant activity against carbon tetrachloride induced liver injury in rats 49 .…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…The high rate of wound contraction, decrease in the period for epithelialization, high skin breaking strength were observed in animals treated with 10% leaf extract ointment when compared to the control group of animals. It has been reported that tannins possess the ability to increase the collagen content, which is one of the factors for the promotion of wound healing 48,2 .…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Animals were given free access to water and were fasted for 24 hours before the experiment. 16 Edema was created by injecting 0.1 mL of 1% w/v carrageenan in saline into the rat's right hind leg plantar side an hour before each experiment. Utilizing the index finger, lightly brush the planting region of the chest paw 50 times before applying 0.2 g of ointment.…”
Section: In-vivo Anti-inflammatory Studymentioning
confidence: 99%